2020
DOI: 10.1111/jcmm.14939
|View full text |Cite
|
Sign up to set email alerts
|

Nusinersen treatment and cerebrospinal fluid neurofilaments: An explorative study on Spinal Muscular Atrophy type 3 patients

Abstract: The antisense oligonucleotide Nusinersen has been recently licensed to treat spinal muscular atrophy (SMA). Since SMA type 3 is characterized by variable phenotype and milder progression, biomarkers of early treatment response are urgently needed. We investigated the cerebrospinal fluid (CSF) concentration of neurofilaments in SMA type 3 patients treated with Nusinersen as a potential biomarker of treatment efficacy. The concentration of phosphorylated neurofilaments heavy chain (pNfH) and light chain (NfL) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 17 publications
5
64
0
2
Order By: Relevance
“…Similar results were confirmed in plasma in the ENDEAR study in symptomatic SMA type I patients [ 85 ]. In older patients with less severe forms of SMA, the role of NFs has not yet been confirmed probably as consequence of a slower disease progression [ 86 , 87 ]. SMN protein regulates RNA metabolism and biogenesis of microRNA (miRNA), which are gene expression modulators, and their dysregulation is implicated in a variety of neuromuscular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were confirmed in plasma in the ENDEAR study in symptomatic SMA type I patients [ 85 ]. In older patients with less severe forms of SMA, the role of NFs has not yet been confirmed probably as consequence of a slower disease progression [ 86 , 87 ]. SMN protein regulates RNA metabolism and biogenesis of microRNA (miRNA), which are gene expression modulators, and their dysregulation is implicated in a variety of neuromuscular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Independent studies exploring this aspect showed a consistent range of HFMSE score: between 0 and 20 for type 2 and between 25 and 66 for type 3 patients [ 27 , 28 , 29 ]. A larger range was recorded for the type 3 patients followed up by Walter and colleagues [ 18 ].…”
Section: Evaluation Of Functional Outcomes In Adult Patientsmentioning
confidence: 99%
“…Results differed between SMA types 2 and 3, with a higher average HFMSE increase for SMA type 3 patients. Interestingly, no correlation was observed between the age at treatment and the evolution of the functional score during the treatment [ 19 , 29 ].…”
Section: Evaluation Of Functional Outcomes In Adult Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Od 1 stycznia 2019 roku w Polsce wprowadzono leczenie przy wykorzystaniu nusinersenu (spinraza)pierwszego leku leczącego przyczynę SMA. Lek ten jest oligonukleotydem modyfikującym wadliwy splicing pre--mRNA genu SMN2 [1,4,7,8]. Ze względu na ciągłą konieczność rehabilitacji oraz świadomości stopnia progresji choroby konieczne jest używanie przez fizjoterapeutów zwalidowanych narzędzi diagnostycznych oceniających poziom funkcjonalny dziecka z SMA.…”
unclassified